Wastage of rarest blood and blood components can be stopped: 9 years retrospective and cross-sectional study at tertiary hospital - Namdhari, Balkrishna H.; Bharati, Tapasya V.; Shinde, Ashish P. (International Journal of Research in Medical Sciences, 2018)
Background: Inventory of blood/blood components suffer due to outdating of Rh Negative units. Rationale of this article is strategy of transfusion of O Rh Negative red cells to all. A Rh Negative red cells can be given to A Rh Positive, AB Rh Positive. B Rh Negative red cells can be given to B Rh Positive, AB Rh Positive. AB Rh Negative red cells to AB Rh Positive recipients. AB Rh Negative FFP/PRP can be given to all. Objective was to avoid out dating of Rh Negatives by studying the percentage of outdated Rh Negative units amongst the all outdated. Methods: This was 9 years observational, retrospective, cross sectional and descriptive study conducted at tertiary care hospital. Outdated units of Rh Negative blood and components were analysed from the year wise discard registers of blood bank. Percentage of Rh Negative units within all outdated units were calculated. Results: 198 Rh Negative units of whole blood and blood components within all outdated units was 29.11%. Out of 198 the 20 Rh Negative blood components were discarded. Conclusions: Adopt type and screen protocol to prevent outdating. Avoid to bleed the rare blood groups. Audit by hospital transfusion committee and implementation of MSBOS. Track O Rh Negative red cells transfusion to Rh Positive as quality indicator. Track/review transfusion of O Rh negative red cells to Non O Rh negative recipients. Track AB Rh Negative FFP/PRP transfusions to all.